Pengolahan Limbah Cair Laboratorium Kimia Menggunakan Metode Elektrokoagulasi - Yulia Sukmawardani; Vina Amalia (Jurnal Kartika Kimia, 2019)
Laboratory liquid waste is one of the problems encountered in universities. Before discharged into the aquatic environment, the liquid waste must pass through the processing first. One way that can be done to reduce the contamination of laboratory waste is by lowering the heavy metal content contained in the waste by using electrocoagulation method. Electrocoagulation becomes one of the alternative waste treatment because this method is easy and simple to do, but produces high efficiency of metal removal. In this research has been tested the liquid waste treatment laboratory by using electrocoagulation method. The processing of liquid waste by electrocoagulation using Al-Al electrodes, gives a very significant metal removal result. Including decreased levels of organic compounds and total solids in waste decreased. However, the waste from the treatment with electrocoagulation has not met the required quality standard in West Java Provincial Regulation No. 6 of 1999 on the Standard of Waste Water Quality. Because of the high concentration of metal in laboratory liquid waste, it is necessary to process the waste before and after the electrocoagulation process. Keywords: Al electrode, electrocoagulation, laboratory liquid waste